Successful treatment with refractory myasthenia gravis that developed after allogeneic hematopoietic stem cell transplantation: two case reports - Zhang, Huili; Wen, Yi; Ou, Yaotong; Chen, Xi; Peng, Yu; Lai, Mingjun; Mo, Wenjian; Wang, Honghao (Frontiers in Immunology, 2025)
IntroductionMyasthenia gravis (MG) is an autoimmune disorder caused by autoantibodies that target the neuromuscular junction, leading to muscle weakness and fatigability. Diagnosis is based on clinical presentation, confirmation of the presence of AChR-Ab, characteristic electromyography findings, and clinical improvement after administration of acetylcholinesterase inhibitors.MG is often associated with thymoma and other autoimmune diseases, but it is rare following allo-HSCT.Case reportwe reports two rare cases of MG after transplantation, including the first case of post-transplantation double-antibody-positive MG. Patient 1 was a 45-year-old woman diagnosed with B-cell acute lymphoblastic leukemia. She underwent haploidentical allo-HSCT from a female donor (5/10 matching human leukocyte antigens [HLAs]) and developed graft-versus-host disease (GVHD) after transplantation. At 42 months after transplantation, the patient developed episodic generalized weakness, dysarthria, dysphagia, and axial weakness. The serum anti-acetylcholine receptor antibodies (AchR-Abs) level was > 20 nmol/L (normal range: < 0.4 nmol/L). She was diagnosed with MG type IIb according to the Myasthenia Gravis Foundation of America classification. At 44 months post-transplantation, the patient began to experience episodic cramps, Electromyography (EMG) revealed a small number of fibrillation potentials with the right thumb extensor and the right anterior tibial muscle in a relaxed state, as well as spastic discharge, considered indicative of cramp–fasciculation syndrome (CFS). Improvement was seen following treatment with carbamazepine. Patient 2 was a 49-year-old man diagnosed with acute myeloid leukemia. He underwent haploidentical allo-HSCT from his son and did not develop GVHD. At 23 months post-transplant, the patient experienced recurrent diplopia, ptosis, axial weakness, and dyspnea. Neostigmine and repetitive nerve stimulation tests were positive, the level of anti-AChR IgG antibodies and MuSK receptor antibodies were positive, leading to a diagnosis of type IVb MG. The symptoms were mostly relieved after rituximab treatment.DiscussionThis article reports two rare cases of MG after transplantation, including the first case of post-transplantation double-antibody-positive MG, and reviews the general clinical characteristics of MG cases after allo-HSCT reported in previous literature. These cases enhance our understanding of MG following transplantation and add to the data on post-transplantation MG.